1989
DOI: 10.1113/jphysiol.1989.sp017805
|View full text |Cite
|
Sign up to set email alerts
|

Activation and desensitization mechanisms of muscarinic current response in single pancreatic acinar cells of rats.

Abstract: 3. The sensitivity of 1P3 recovers after short-term administration of ACh (0 2 ,tM), and in turn, the ACh-induced response is augmented by the presence of internal IP3. These results suggest that a synergism between IP3 and another ACh-induced substance plays an important role in muscarinic Ca2+ signalling.4. ACh-induced responses are inhibited by pre-incubation (10 min) with an activator of protein kinase C, TPA (12-O-tetradecanoylphorbol-13-acetate, 16 nM), or augmented by pre-incubation (10 min) with an inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
40
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 32 publications
11
40
1
Order By: Relevance
“…9B). The present finding that Ca2+ oscillations subsist after protein kinase C inhibition is in agreement with a recent report that H7 does not affect Ca2+ waves in the exocrine pancreas (Maruyama, 1989). appears more reliable than the first, probably because onset kinetics reflect more directly the first steps of the Ca2+ release response than does the peak Ca2+ value (Horn & Marty, 1988).…”
Section: Lack Of Effect Of Protein Kinase C On Calcium Oscillationssupporting
confidence: 82%
See 1 more Smart Citation
“…9B). The present finding that Ca2+ oscillations subsist after protein kinase C inhibition is in agreement with a recent report that H7 does not affect Ca2+ waves in the exocrine pancreas (Maruyama, 1989). appears more reliable than the first, probably because onset kinetics reflect more directly the first steps of the Ca2+ release response than does the peak Ca2+ value (Horn & Marty, 1988).…”
Section: Lack Of Effect Of Protein Kinase C On Calcium Oscillationssupporting
confidence: 82%
“…rat hippocampal slices: Labarca, Janowsky, Patel & Paul, 1984;human platelets: MacIntyre, McNicol & Drummond, 1985;Zavoico, Halenda, Sha'afi & Feinstein, 1985;PC12 cells: Vicentini, Virgilio, Ambrosini, Pozzan & Meldolesi, 1985; murine neuroblastoma cells: Kanba, Kanba & Richelson, 1986; exocrine glands: Llano & Marty, 1987;Sugiya, Obie & Putney, 1988; Maruyama, 1989; but see Gray, 1988), it has been found that protein kinase C activators inhibit the production of inositol trisphosphate and the ensuing Ca2+ rise, thus suggesting the presence of a negative feedback due to the production of diacylglycerol by phospholipase C. Whether or not this inhibition actually participates in desensitization is, however, unclear. In a liver cell line, downregulation of protein kinase C induced by prolonged treatment with phorbol esters has recently been shown to potentiate and to prolong the inositide response, suggesting that protein kinase C inhibition may play a role in agonist-induced desensitization (Hepler, Earp & Harden, 1988).…”
Section: Y P Tan and A Martymentioning
confidence: 99%
“…This has already been shown for M 3 receptors in other cell systems (Yamatani et al 1988, Maruyama 1989, Tan & Marty 1991, reviewed by Berrie & Elliott 1994. However, the observation that desensitization of PLC-coupled muscarinic receptors is mediated by PKC (Haga et al 1990) is not supported by all studies as described by Benya et al (1995).…”
Section: Pkc Involvement In Desensitizationsupporting
confidence: 60%
“…In rat clonal pituitary cells (Ozawa & Kimura, 1979;Ozawa, 1981;Dubinsky & Oxford, 1985;Ritchie, 1987b;Mollard et al 1988), thyrotrophin-releasing hormone (TRH) initiates an initial activation of Ca2+-dependent K+ current followed by a secondary increase in action potential frequency. A similar transient activation of outward current occurs in response to muscarine in a number of inexcitable secretary cells (Trautman & Marty, 1984;Horn & Marty, 1988;Gray, 1988;Maruyama, 1989). Despite the widespread occurrence of a hyperpolarizing response during the initial stages of secretagogue action, there is no clear functional role for this type of effect in secretary cells (Petersen & Murayama, 1984).…”
mentioning
confidence: 99%
“…Although our results cannot exclude the possibility that a critical dialysissensitive component is slowly lost during our recordings, the fact that the ability of muscarine to produce elevations of cytosolic Ca2+ undergoes some essentially irreversible deterioration even in non-dialysed cells implies that the loss of muscarinic sensitivity may reflect some intrinsic property of the muscarinic response, rather than a limitation of the experimental approach. Such desensitization is not uncharacteristic of muscarinic-mediated processes involving PLC (Llano & Marty, 1987;Maruyama, 1989). …”
mentioning
confidence: 99%